Localisation of politics and local electoral participation. Issue 1 (2nd January 2023) - Kukec, Marko
ABSTRACT: Nationalisation of politics generally decreased the voter participation at municipal elections by lowering their salience, but the variation in nationalisation has been underestimated. Leveraging variation in two dimensions of localisation of municipal political competition – ethnic minority concentration and number of non-partisan local lists – this paper tests whether increased stakes and salience at 'localised' municipal elections increase electoral participation in respective municipalities. Based on the data from Croatian local elections (2001–2017), non-partisan lists drive voter participation, particularly in smaller municipalities. The effect of ethnic minority concentration depends on the minority status of the ethnic group within a municipality.